Pengaruh Produk, Harga, Promosi, Dan Lokasi Terhadap Keputusan Pembelian Pelanggan Toko Muhammadiyah Bisnis Center (MBC) Kota Metro - Suryadi, Suryadi; Yateno, Yateno; Kurnia, Dewi (Universitas Muhammadiyah Metro, 2023)
The purpose of this research is to determine 1) the partial effect of the product on purchasing decisions, 2) price on purchasing decisions, 3) promotion on purchasing decisions, 4) location on purchasing decisions, and 5) simultaneously on purchasing decisions. The design of this research is a quantitative method. With a total population of 14,155 respondents for 30 days, while the sample calculation found 100 respondents. The sampling technique is purposive sampling. The data collection method uses a questionnaire by sharing it with consumers who often make transactions at Muhammadiyah Bisnis Center store in Metro City. And the analysis tool uses validity, reliability and multiple regression results with the decision to use a partial test (t), test together and the coefficient of determination. The analysis results conclude that purchasing decisions can be understood by consumer behaviour and how consumers make purchasing decisions. So the combination of the retail mix elements (Retailing mix) of products, prices, promotions, and the right location by retailers is expected to attract the target market through consumer purchases.